Building cyber defense skills: the CipherQuest educational CTF framework - Mahmod Attar Bashi, Zainab Senan; Abd Rasid, Muhammad Aliff Iman; Mohd Razmi, Muhammad Alif Haziq; Sakka, Oula; Mohd Aman, Azana Hafizah (PENERBIT UniMAP, 2026)
As cyber threats grow increasingly sophisticated, equipping the next generation of cybersecurity professionals with practical, engaging training methods has never been more critical. Current cybersecurity education approaches face three key limitations: (1) traditional open-source CTF platforms often lack pedagogical alignment with academic curricula and lack institutional-grade user management and assessment tools, (2) game-based learning tools frequently sacrifice technical depth for accessibility, and (3) simulation environments may fail to foster competitive engagement crucial for skill retention. This paper evaluates three innovative approaches for cybersecurity education: Capture-the-Flag (CTF) competitions using the Ionian CTF model, which develops practical skills through challenge-based learning; CyberMoraba, an adaptation of the traditional African strategy game Morabaraba redesigned for cybersecurity instruction; and Cyberattack Simulator, offering realistic threat defense scenarios. Comparative analysis identified CTF as the most effective method for university students, combining technical skill development with competitive learning dynamics. Therefore, CipherQuest was developed, a CTF platform that synthesizes best practices from established systems (picoCTF, CryptoHack, HackTheBox) while incorporating IIUM curriculum-aligned challenges. The platform features jeopardy-style challenges across security domains with real-time feedback and progress tracking. Preliminary results show 90% of participants demonstrated improved cybersecurity knowledge and skills transferable to real-world scenarios. This research establishes that structured CTF platforms can effectively bridge theoretical cybersecurity education and practical application while maintaining academic consistency. The CipherQuest platform can provide universities with an evidence-based model for implementing engaging cybersecurity training that meets both educational objectives and industry needs.